EXCISION OF GIANT CELL TUMOR FOLLOWED BY RECONSTRUCTION OF DISTAL RADIUS USING FREE VASCULARIZED FIBULAR GRAFT - Prisca Oriana Sutanto; Agus Roy Rusli Hamid; Adinda Putra Pradhana (Indoscholar, 2018)
Giant cell tumor (GCT) of the distal radius is a rare and unpredictable lesion. The aim of treatment is complete removal of the tumor and preservation of the maximum function of the extremity. Lower rates of local recurrence have been noted after wide resection of the diseased bone. Its standard treatment has ranged from surgical curettage to wide resection. One method for closing the defect is using the head of the fibula as a substitute for the distal radius. The healing of vascularized fibular graft is very quick and without bone resorption. Thus, in the procedure for reconstruction and limb salvage after bone tumor resection of the distal radius, the free vascularized fibular graft with the fibular head is an ideal substitute. This case report will show a patient with GCT that successfully treated by an excision of GCT followed by reconstruction of distal radius using free vascularized fibular graft.